2012
DOI: 10.1152/jn.00900.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated mean and functional connectivity BOLD signals in visual cortex during eyes closed and fixation

Abstract: We investigated the effects of resting state type on blood oxygen level-dependent (BOLD) signal and functional connectivity in two paradigms: participants either alternated between fixation and eyes closed or maintained fixation or eyes closed throughout each scan. The BOLD signal and functional connectivity of lower and higher tiers of the visual cortical hierarchy were found to be differentially modulated during eyes closed versus fixation. Fixation was associated with greater mean BOLD signals in primary vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 68 publications
4
25
0
Order By: Relevance
“…In sighted adults, occipital and frontal cortices interact during visual attention and visual working memory tasks (Zanto, Rubens, Thangavel, & Gazzaley, 2011;Moore & Armstrong, 2003;Kastner & Ungerleider, 2000;Miller, Erickson, & Desimone, 1996). There is also some evidence that in the absence of a task, fronto-occipital correlations are higher in sighted individuals during visually attentive states (Liu, Dong, Zuo, Wang, & Zang, 2013;McAvoy et al, 2012), although these correlations are substantially more restricted in spatial extent than those observed here. Increased fronto-occipital connectivity in blind individuals could reflect an expansion and repurposing of this functional connection for nonvisual processing.…”
Section: Implications Of Resting State Group Differences For Anatomy mentioning
confidence: 49%
“…In sighted adults, occipital and frontal cortices interact during visual attention and visual working memory tasks (Zanto, Rubens, Thangavel, & Gazzaley, 2011;Moore & Armstrong, 2003;Kastner & Ungerleider, 2000;Miller, Erickson, & Desimone, 1996). There is also some evidence that in the absence of a task, fronto-occipital correlations are higher in sighted individuals during visually attentive states (Liu, Dong, Zuo, Wang, & Zang, 2013;McAvoy et al, 2012), although these correlations are substantially more restricted in spatial extent than those observed here. Increased fronto-occipital connectivity in blind individuals could reflect an expansion and repurposing of this functional connection for nonvisual processing.…”
Section: Implications Of Resting State Group Differences For Anatomy mentioning
confidence: 49%
“…This result is consistent with a previous resting state fMRI study by Li and colleagues (Li et al, 2000) who used a seed-based approach and found reduced connectivity within visual cortex due to cocaine, a potent releaser of synaptic dopamine. One interpretation of this finding is in terms growing evidence that links diminished neuronal coherence within visual cortex, especially between homotopic regions, with enhanced attentional states—for example eyes open versus eyes closed rest (McAvoy et al, 2012) and strong visual stimulation (Nauhaus et al, 2009). This hypothesis is further supported by a pharmaco-fMRI study (Ricciardi et al, 2012) that found physostigmine, an acetecholinesterase inhibitor that increases alertness and attention, reduces connectivity within the visual network during attention processing.…”
Section: Discussionmentioning
confidence: 96%
“…Existing circuit models propose dopamine-mediated interactions between striatum and motor cortex (Alexander et al, 1986) as well as striatum and cerebellum (Hoshi et al, 2005), and previous fMRI studies with acute administration of dopamine modulators [L-dihydroxyphenylalanine (L-Dopa), cocaine] found altered connectivity in multiple motor regions including striatum, cerebellum, and motor cortex (Cole et al, 2012; Kelly et al, 2009; Li et al, 2000). Additionally, Li and colleagues (2000) found that cocaine reduced connectivity within visual cortex, with evidence suggesting that greater decoherence in visual cortex is associated with high attention states (McAvoy et al, 2012; Nauhaus et al, 2009). Thus we predicted that MPD would modulate resting state connectivity in motor regions including striatum, somatomomotor network, and cerebellum, and would reduce connectivity within visual network.…”
mentioning
confidence: 99%
“…Indeed, most studies do converge on similar network patterns even across a variety of behavioral states (e.g. eyes closed, open, or open and fixating; Bianciardi et al, 2009; but see McAvoy et al, 2012) though there are also subtle, but important, differences in the patterns across both normal and diseased states (for reviews, see Greicius, 2008; Heine et al, 2012; Menon, 2011). The univariate and multivariate approaches typically applied to resting-state data (for review, see Cole et al, 2010) assume that the strength of interactions between regions is constant over time.…”
Section: Introductionmentioning
confidence: 99%